Desain dan Implementasi Komik Digital Edukatif pada Pembelajaran Akidah Akhlak Siswa Kelas V Madrasah Ibtidaiyah - Nashihatun Nabilah; Lailatus Shofiyah; Ririn Inayatul Mahfudloh (JOIN: Journal of Indonesian Education and Learning, 2026)
This study aims to develop educational digital comic–based learning media as aninnovation in educational technology for the Akidah Akhlak subject, focusing ondiscipline and independence behavior for fifth-grade students at MI Hidayatul Ulum.The research employed a Research and Development (R&D) method using the ADDIEmodel, which consists of analysis, design, development, implementation, and evaluationstages. The digital comic learning media were developed using Canva for illustrationdesign and CapCut for audio processing and digital media compilation. The researchsubjects consisted of 25 fifth-grade students at MI Hidayatul Ulum. Data collectiontechniques included observation, interviews, and student response questionnaires.The results showed that the educational digital comic learning media achieved aneffectiveness level of 83.44%, categorized as effective, and a feasibility level of 84.37%,categorized as very feasible. The media were able to enhance students’ learninginterest, motivation, and understanding of discipline and independence values throughcontextual storytelling, attractive illustrations, and easy-to-understand language.Therefore, the educational digital comic learning media are feasible and effective tobe used as an alternative learning medium for Akidah Akhlak in Madrasah Ibtidaiyah.